320 THE POTENTIAL ROLE OF ECHOCARDIOGRAPHY IN THE PRE-PARTICIPATION SCREENING: RESULTS OF AN OBSERVATIONAL RETROSPECTIVE STUDY. (15th December 2022) - Donati, Federica; Guicciardi, Claudio; Lodi, Elisa; Modena, Maria Grazia; Palermi, Stefano; Biffi, Alessandro; Fernando, Frederick
Abstract: Introduction: Preparticipation screenings (PPs) have been conceived for the potential to prevent SCD in young athletes by early identification of hidden cardiac diseases. Commonly used protocols include history collection, physical examination and baseline electrocardiogram. Nevertheless, transthoracic echocardiography has been hypothesized to have a primary role in the PPs. Aim of the Study: The aim of the present paper was to evaluate the potential role of echocardiogram in identifying life-threatening cardiovascular abnormalities that might be undetected by commonly used PPS. Methods: We retrospectively reviewed a corporate wellness program - database and analyzed data recorded from 2017 to 2022 to compare two medical models: a "standard" PPS including medical history, physical examination, electrocardiogram (ECG) and exercise stress test (EST); an "advanced" PPS comprising history, physical examination, ECG, EST and echocardiography. The primary outcome of the study was to assess the efficacy of the advanced PPS in detecting CV abnormalities compared to the "standard" PPS. Results: We analyzed data from 500 subjects (420 male, 33.69 ± 7.9 mean aged) enrolled for the first time in the corporate wellness program between 2017 and 2022. 339 (67.8%) subjects had no pathological findings at "standard" PPS and, even if would have not required further evaluation including echocardiogram, performed the ultrasound exam anyway ("advanced" PPS): 31 (9.1%) showed some abnormal findings at echocardiography. Conclusions: Even if with some limitations, performing a screening echocardiogram could help to detect subjects with some form of cardiovascular morpho-functional abnormalities, otherwise difficult to diagnose with "standard" PPS protocol.